OREXIN, STRESS AND ANXIETY/PANIC STATES - Johnson, Philip L. (2012)
A panic response is an adaptive response to deal with an imminent threat and consists of an integrated pattern of behavioral (aggression, fleeing or freezing) and increased cardiorespiratory and endocrine responses that are highly conserved across vertebrate species. In the 1920’s and 1940’s Philip Bard and Walter Hess respectively determined that the posterior regions of the hypothalamus are critical for a “fight-or-flight” reaction to deal with an imminent threat. Since the 1940’s it was determined that the posterior hypothalamic panic area was located dorsal (perifornical nucleus: PeF) and dorsomedial (dorsomedial hypothalamus: DMH) to the fornix. This area is also critical for regulating circadian rhythms and in 1998, a novel wake-promoting neuropeptide called orexin/hypocretin (ORX) was discovered and determined to be almost exclusively synthesized in the DMH/PeF and adjacent lateral hypothalamus. The most proximally emergent role of ORX is in regulation of wakefulness through interactions with efferent systems that mediate arousal and energy homeostasis. A hypoactive ORX system is also linked to narcolepsy. However, ORX’s role in more complex emotional responses is emerging in more recent studies where ORX is linked to depression and anxiety states. Here we review data that, demonstrates ORX’s ability to mobilize a coordinated adaptive panic/defence response (anxiety, cardiorespiratory and endocrine components), and summarize the evidence that supports a hyperactive ORX system being linked to pathological panic and anxiety states.